1987
DOI: 10.1161/01.hyp.9.6_pt_2.iii64
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-induced hypertension in the dog.

Abstract: To study the relationship between body weight and blood pressure, we have developed an animal model of obestiy-induced hypertension. Nine adult mongrel dogs were chronically instrumented with aortic and vena caval catheters. After a 2-week control period, all dogs were made to gain weight by adding 2 Ib/day of beef fat to their diet for 5 weeks. Blood pressure, heart rate, and body weight were measured daily before the addition of dietary fat, during the 5 weeks of the high fat diet, and for 6 weeks after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
0
5

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 14 publications
8
72
0
5
Order By: Relevance
“…As in this work, Brown et al (2007) observed that overweight dogs possessed higher reference range arterial pressures in relation to those of ideal body weight. As such, food restriction is considered an important non-pharmacological treatment for controlling arterial pressure, especially in dogs of excessive weight (Rocchini et al 1987, Rocchini et al 1989.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in this work, Brown et al (2007) observed that overweight dogs possessed higher reference range arterial pressures in relation to those of ideal body weight. As such, food restriction is considered an important non-pharmacological treatment for controlling arterial pressure, especially in dogs of excessive weight (Rocchini et al 1987, Rocchini et al 1989.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the weight loss program it was observed that the analyzed variables gradually returned to their basal values (Rocchini et al 1987).…”
Section: Introductionmentioning
confidence: 98%
“…[9][10][11] This could, like sympathetic overactivation, explain the tachycardia and the increased risk of cardiovascular mortality through hypertension and sudden cardiac death 9,12 in obese patients. Using a canine model of dietary-induced obesity (dogs fed a high-fat diet), which mimics many of the characteristics of human obesity, [13][14][15] we observed atrial muscarinic receptor downregulation 16 and a decreased high frequency power (HF) of heart rate variability (HRV), which reflects cardiac parasympathetic activity. Both of these modifications led to tachycardia, and demonstrate a defective cardiac parasympathetic system.…”
Section: Introductionmentioning
confidence: 99%
“…9 Elevated PRA has likewise The renin-angiotensin system (RAS) is a powerful been found in dogs after 5 weeks on a high-fat diet, humoral regulator of fluid volume and blood pressdespite marked sodium retention and increased ure (BP). 1,2 Despite the effectiveness of pharmacolextracellular fluid volume.…”
Section: Introductionmentioning
confidence: 99%
“…Although obesity is the weight, BP and the RAS have been infrequent. [9][10][11][12][13] most important single modifiable risk factor for Rochini et al 9 reported increased aldosterone hypertension, little is known about the mechanism linking the two conditions. We initiated a com- approximately balanced between persons above and *P Ͻ 0.000; **P Ͻ 0.05; ***P Ͻ 0.01 between obese and nonbelow the 140/90 hypertension cut-point were obese groups.…”
Section: Introductionmentioning
confidence: 99%